Habitat differentiation between groups of Risso's dolphins as evidence of coastal nursery areas - Fernandez, Marc (2012)
Previous studies have shown strong site fidelity by Risso's dolphins at a site off Pico Island, Azores. Females with calves tend to be seen together, often with newborn calves. In this study we analyse position and photo-identification data gathered on ocean surveys from 2004 to 2007 to look at the distribution of females with calves of different ages (newborns to 6 months old, 6 months to 2 years and 2 to 4 years) and compare it with pods with no calves present. The association of the different groups with selected ecogeographical variables was tested, and a maximum entropy model was used to create habitat suitability maps, using a 50mx50m grid. The female pods with younger calves were found to have a significantly distinct distribution from those with older calves or without calves. The main difference was that the pods with younger calves tended to be found closer to the shore, whereas the other groups used a wider offshore area. More extensive sampling is required in order to validate the existence and geographical distribution of coastal nursery areas for this species. However, we believe the present data is enough to elicit precautionary conservation measures to reduce human impact on a vulnerable part of the dolphin society, such as that associated with boat traffic, whale watching and swimming with dolphins operations.